THE ROLE OF ALISHER NAVOI IN THE EASTERN KHAMSA - Ismailova Nigora Mirzoaliyevna (Journal of Learning on History and Social Sciences, 2024)
While writing his work, the creator pays attention to every word of it. Although the work "Khamsa" was written by poets before Navoi, Navoi was very confused in choosing names for each of the characters in his "Khamsa"